(untitled) (Research, Society and Development, 2020)
The main purpose of this work is to perform a thermal analysis in an air conditioning duct to verify the influence of the thermal properties of the insulating material on the minimum thermal insulation thickness necessary to avoid the condensation of water vapor present in the air. The mathematical formulation is based on Fourier’s law and the first law of thermodynamics. A response surface, a contour plot and a mathematical model for the analyzed response variable, were obtained from an experimental design. Results indicate that the reduction of thermal conductivity and increase of emissivity of the insulating material contribute to the reduction of the minimum thermal insulation thickness.